2009
DOI: 10.2478/v10032-009-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Postharvest Treatment and Type of Packaging on Quality and Storage Ability of Cauliflower (Brassica oleracea L. var. botrytis)

Abstract: The Influence of Postharvest Treatment and Type of Packaging on Quality and Storage Ability of Cauliflower (Brassica oleracea L. var. botrytis) The influence of postharvest hot and cold water treatments on the quality and storage ability of cauliflowers were studied. Also the usefulness of different type of unit packaging for cauliflower storage was compared. The cauliflower heads of Fremont F1 cultivar, after different treatments, were stored at 0°C for six weeks. Postharvest hot water treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to the research of Grzegorzewska et al (2009) and Xue et al (2021), the temperature setting, number of storage days, and CaCl 2 solution concentration of this experiment were determined [18,21].…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research of Grzegorzewska et al (2009) and Xue et al (2021), the temperature setting, number of storage days, and CaCl 2 solution concentration of this experiment were determined [18,21].…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…Yang et al (2016) found that CaCl 2 treatment can increase glutamine biosynthesis in broccoli, promote myrosinase (MYR) gene expression and activity, and improve the total antioxidant capacity and DPPH scavenging capacity [17]. Grzegorzewska et al (2009) found that, during the storage period, broccoli treated with ice water had a lower rooting rate, lower loss of tightness, and minor color change [18]. Some research reports have shown that CaCl 2 treatment combined with other methods is a good method of fruit and vegetable preservation.…”
Section: Introductionmentioning
confidence: 99%